Identifying Biomarkers of Neuroplasticity Associated with Exercise-Induced Cognitive Change in Older Adults with MCI. - Savettiere, Adriana; Louras, Peter; Langdon, Sarah; Fairchild, J. Kaci (Experimental Aging Research)
Objectives: This exploratory study aimed to identify biomarkers of neuroplasticity that prevent cognitive decline. This study examined activity-dependent changes in the neurologic proteome that contributed to post-exercise improvements in processing speed in older adults with mild cognitive impairment (MCI). Methods: Participants included 20 older adult Veterans with MCI recruited through the VA Palo Alto Health Care System (VAPAHCS) who participated in moderate-high intensity water-based activity thrice weekly for six months. Plasma protein concentration was measured using the Olink Target 96 Neurology Assay. Processing speed measures included the Trail Making Test Trial A (TMT-A), the Stroop Color (SC) and Word (SW) trials, and the Symbol Digit Modalities Test (SDMT). Results: Preliminary analyses revealed two proteins of interest: neuropilin-2 (NRP2) and neuroblastoma suppressor of tumorigenicity 1 (NBL1). Primary analyses used mixed effects models to determine the impact of changes in neurologic-related proteins on changes in processing speed after exercise. Results indicated that decreased levels of NRP2 were associated with improved outcomes on the SDMT after exercise. In contrast, changes in NBL1 had no significant effect on the relationship between exercise and processing speed. Conclusion: These results support previous research linking NRP2 function to synaptic plasticity downscaling and present NRP2 as a potential target for cognitive intervention.